Sekolah Damai di Desa Nglinggi - Maulana Iskandar; Lutfi Fadilah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Peace school is a non-formal education activity initiated by local facilitator Wahid Foundation which aims to foster a culture of peace in grassroots communities, especially at the children's level. Data were collected by using observation, documentation, and interview methods. The data that has been collected is then processed and analyzed with the following steps, namely data reduction, data presentation, and conclusion. The results of the peaceful school research show several points as follows, firstly the peace school was initiated by the Damai Village coordinator. Second, the school of peace aims to create positive peace. Third, the peace school supports the peacebuilding movement as well as helps the local people's economy.